Gesundheitliche Langzeitfolgen psychosozialer Belastungen in der Kindheit: ein Update = Health-related long-term effects of adverse childhood experiences : an update - Egle, Ulrich Tiber; Cierpka, Manfred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
In the last decade strong empirical evidence from several long-term studies supports the conclusion that physical and sexual abuse as well as emotional deprivation in childhood make people significantly more vulnerable to mental and functional disorders across their lifetime. Additionally, an increased vulnerability to several somatic disorders (cardiovascular disorders, type-2-diabetes, hepatitis, chronic obstructive pulmonary disease (COPD), immunological and pain disorders, pharynx and lung cancer) was demonstrated - most of them with a reduced life expectancy. A review of the current research will be presented that outlines the underlying developmental neurobiological and psychological mechanisms mediating these long-term effects. There is now sufficient evidence about familial risk constellations that demonstrates the well-documented impact of specific prevention strategies by several model projects. Only by establishing these strategies, future enormous health-related burdens and high economic costs (unfitness to work, early retirement) can presumably be limited.
Gesehen am 31.08.2017